Pengaruh Likuiditas Dan Profitabilitas Terhadap Harga Saham (Studi Pada Perusahaan Sub Sektor Tekstil Dan Garmen Periode 2018-2022 Yang Terdaftar Di Bursa Efek Indonesia) - Ilhami, Tia Dian; Rahwana, Kusuma Agdhi; Wibawa, Gian Riksa (Jurnal Bisnis, Manajemen dan Akuntansi, 2024)
The research aims to determine the influence of the Liquidity and Profitability on the share prices of textile and garment companies listed on the Indonesia Stock Exchange for the 2018-2022 period, both simultaneously and partially. This research uses quantitative research methods. The research sample was 13 textile and garment manufacturing companies obtained using a sampling technique, namely purposive sampling. The analytical tool used in this research is panel data regression using eviews 12. The research results show that partially the Liquidity variable does not have a significant effect on stock prices, while the Profitability variable has a significant effect on stock price in the sector. Textiles and garments listed on the IDX for the 2018-2011 period. Simultaneously, the variables Liquidity and Profitability have a significant effect on stock prices in the textile and garment sector listed on the IDX for the 2018-2022 period.